Evaluation of Health System Development Plan and Basic Education Transformation Plan Based on Health System Assumptions with Emphasis on Education - Mohammad Azimi (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Health education and health promotion are considered an important source for economic, social and individual development. It is the governments' important role to consider it as a crusial matter and all human beings need training to achieve this worthwhile goal, namely health. Methods: This study was carried out using content analysis "Shannon Entropy". In this method data processing is done with a new look and both quantitative and qualitative content analysis. Entropy is an index to measure the uncertainty, and probability distribution. The content of the responsive design (text layout and healthcare reform basic education development plan) and twelve main dimensions and 58 sub-components of health education and health promotion were examined. Results: Analizing the data of Shannon entropy analysis showed that the prevention of disease (32 cases) is the most frequent factor, and the least amount belonged to physical activity, mental health, prevention of high-risk behavior and disabilities with the frequency of 0. Studying the whole document of fundamental transformation, the component of the mental health (97 cases) is the most frequent, and the least frequent component was disability (0 cases). Conclusion: The results of the frequency of components have shown that the components of the health system do not have the normal distribution. Unfortunately, very little health education and health promotion are discussed in this document.